2018
DOI: 10.1080/21553769.2018.1552628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of plant genetic diversity in shaping the microbial community structure of Vitis vinifera phyllosphere in the Mediterranean

Abstract: The aerial surface of the plant (phyllosphere) is the habitat of complex microbial communities and the structure of this microbiome may be dependent on plant genetic factors, local environment or interactions between them. In this study, we explored the microbial diversity present in the phyllosphere of a very diverse set of grapevine cultivars representing the three genetic pools of the species, grown on an experimental plot at Montpellier (French Mediterranean region). We assessed microbiome variation in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
3
18
0
Order By: Relevance
“…In contrast to the bacterial communities, the fungal communities were mainly affected by the sampling period, during which PD and evenness showed similar trends for both the biocontrol and Cu-treated leaves. This is in line with Singh et al 31 who showed that the shift of the microbial community in samples collected at different times was detected for fungi only. The fact that phylogenetic diversity increased, together with evenness, until December suggested that the complexity of the fungal community increased due to a higher number of similarly abundant taxa.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast to the bacterial communities, the fungal communities were mainly affected by the sampling period, during which PD and evenness showed similar trends for both the biocontrol and Cu-treated leaves. This is in line with Singh et al 31 who showed that the shift of the microbial community in samples collected at different times was detected for fungi only. The fact that phylogenetic diversity increased, together with evenness, until December suggested that the complexity of the fungal community increased due to a higher number of similarly abundant taxa.…”
Section: Discussionsupporting
confidence: 92%
“…This allowed the conclusion to be drawn that the different amount detected in relative abundance for the Lactobacillaceae family was due to the presence of reads belonging to MW-1. Finally the bacterial community, which appeared to be relatively stable throughout the season, reflected the composition already reported by 31 and 35 . The dominance of Proteobacteria and Firmicutes highlighted in their paper, was consistent with the phyla-distribution shown in the present study.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, we are yet to know what forces determine specific fungal community assemblages (Compant et al, 2016), in particular in woody perennials. Endophytic fungal surveys conducted in woody perennials over the last years showed that plant organ is a significant factor in shaping endophytic fungal assemblage Abdelfattah et al, 2015;Singh et al, 2017;Singh et al, 2018;Ren et al, 2019). In general, the main plant tissues that have been analysed in these studies were vegetative organs, such as leaves, twigs, barks, stems and roots Abdelfattah et al, 2015;Singh et al, 2017;Singh et al, 2018;Ren et al, 2019), and only a few studies have looked for fungal endophytes in reproductive organs (e.g., flowers or fruits) (Abdelfattah et al, 2015;Singh et al, 2018;Ren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%